Kedudukan Akta Notaris Terhadap Hak Cipta Dalam Memberikan Kepastian Hukum Sebagai Jaminan Fidusia - Syamkirana, Ade; Efendi, Abidillah; Marsitiningsih (Pamulang Law Review, 2025)
Fiduciary guarantees in the form of copyright in the making of the deed require the knowledge of the Notary who made the deed and registered the guarantee, especially related to the value of the collateral required in Article 6 of the Fiduciary Guarantee Law to be contained in the Fiduciary Guarantee Deed. This condition in principle has actually been overestimated by experts. First, it is not clear the purpose of mentioning the value of the collateral object in a deed because the amount of the value of the collateral object does not affect the validity of the collateral in question; Second, there is no clarity on who should decide the matter; Third, if the value entered does not match reality, it is not clear who will be responsible for it. However, in connection with this is an absolute requirement of the content of the fiduciary guarantee deed, the determination of the economic value of the object of the guarantee must be carried out as best as possible in order to provide legal certainty for the parties. And in relation to copyright, knowledge is needed related to the proper mechanism for determining economic value so that there is legal certainty for both parties regarding whether the value of the guarantee and the value of the collateral object are appropriate, so that the creditor is harmed because of the inconsistency of the value of the object with the value of the collateral.